Reading performance is not affected by a prism induced increase of horizontal and vertical vergence demand - Dysli, Muriel; Vogel, Nicolas; Abegg, Mathias (Frontiers in Human Neuroscience, 2014)
Purpose Dyslexia is the most common developmental reading disorder that affects language skills. Latent strabismus (heterophoria) has been suspected to be causally involved. Even though phoria correction in dyslexic children is commonly applied, the evidence in support of a benefit is poor. In order to provide experimental evidence on this issue, we simulated phoria in healthy readers by modifying the vergence tone required to maintain binocular alignment. Methods Vergence tone was altered with prisms that were placed in front of one eye in 16 healthy subjects to induce exophoria, esophoria, or vertical phoria. Subjects were to read one paragraph for each condition, from which reading speed was determined. Text comprehension was tested with a forced multiple choice test. Eye movements were recorded during reading and subsequently analysed for saccadic amplitudes, saccades per 10 letters, percentage of regressive (backward) saccades, average fixation duration, first fixation duration on a word, and gaze duration. Results Acute change of horizontal and vertical vergence tone does neither significantly affect reading performance nor reading associated eye movements. Conclusion Prisms in healthy subjects fail to induce a significant change of reading performance. This finding is not compatible with a role of phoria in dyslexia. Our results contrast the proposal for correcting small angle heterophorias in dyslexic children.